THE IMPACT OF LEARNING OFFICES ON SOCIAL SCIENCE LEARNING ACCOMPLISHMENT IN GRADE SCHOOLS - Marsini (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Social Science Education (IPS) as one of the educational programs in the school environment is faced with the challenge of preparing Indonesian people as a whole who are able to take part in the life of modern society. The general goal of social studies education in schools is the achievement of student learning achievement, which in this case is to create citizens who are able to understand their society and are able to actively participate in the process of change and community development. In order to achieve this, one of them must be supported by adequate learning facilities and learning environments. The goal to be achieved in this study is to find out how much influence learning facilities have on student achievement in social studies subjects in class VII SMPN 38 Medan City.This research uses the explanatory survey method, which is a research method intended to find and develop theories, so that the results or research products can explain why or why certain symptoms or social reality occur. The population in this study was all grade VII SMPN 38 Medan City students totaling 17 students. While the research data analysis techniques used are product moment correlation techniques and hypothesis testing techniques used through t tests. Based on the results of the study, it can be concluded that there is an influence of learning facilities on student achievement in social studies subjects in class VIII SMPN 38 Medan City. The resulting correlation magnitude is 0.51. The value is located between 0.40 - 0.599 or medium category. Meanwhile, based on hypothesis testing, it is obtained that the value of t count at the real level of 0.05 is outside the limit of the interval t table (t count > t table = 2.82 > 1.74 or –t calculate < - t table = -2.82 < -1.74). Thus, the hypothesis put forward at the beginning is that there is an influence of learning facilities on student achievement in social studies subjects in grade VII SMPN 38 Medan City is acceptable and has been proven to be true.